2009
DOI: 10.1002/rcm.4082
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sub‐ppb epichlorohydrin levels in water by on‐line solid‐phase extraction liquid chromatography/tandem mass spectrometry

Abstract: 8A new sensitive and selective method based on on-line solid-phase extraction (SPE) coupled 9 to LC(ESI)MS/MS using a triple quadrupole analyzer has been developed for the determination of 10 epichlorohydrin (ECH) in different types of water samples. The great difficulties for ECH direct 11 determination resulting from its low molecular size, high polarity and non-easily ionizable molecule 12 make necessary a previous derivatization step. This previous reaction was optimized employing 3,5-13 difluorobenzylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The DBSs were stored in aluminum bags with desiccant packs. Results suggested that lysosomal enzymes are stable at 4 °C, and no loss activity was noted except for GLA (minus 29.5% if compared to day 0 levels) in agreement with published data (Figures S-2, S-3, and S-4). For the screening purpose, in our center, the median storage time between the drawing of the blood sample and the analysis was 32 h (minimum 20 h, maximum 58 h).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The DBSs were stored in aluminum bags with desiccant packs. Results suggested that lysosomal enzymes are stable at 4 °C, and no loss activity was noted except for GLA (minus 29.5% if compared to day 0 levels) in agreement with published data (Figures S-2, S-3, and S-4). For the screening purpose, in our center, the median storage time between the drawing of the blood sample and the analysis was 32 h (minimum 20 h, maximum 58 h).…”
Section: Resultssupporting
confidence: 91%
“…Many authors used online extraction coupled to LC-MS/MS especially in drug assay applications. 47,48 As far as we know, this is the first use of this analytical approach to detect some LSDs for screening purposes.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…After the extraction, gas chromatography (GC) with electron-capture detector (ECD), flame ionization detector (FID), or mass spectrometry (GC/MS) are used as the analytical apparatus ( Sarzanini et al, 2000 ; Bruzzoniti et al, 2004 ; Ripollés et al, 2009 ). For example, the German method, Water Quality-Determination of Epichlorohydrin , applies the liquid-solid extraction followed by the GC-MS or GC-ECD, which offers a limit of determination of 0.5 μg/L in routine analysis.…”
Section: Introductionmentioning
confidence: 99%